Analisis Biaya Variabel Dan Biaya Tetap Terhadap Penentuan Penjualan Pada Usaha Mikro Kecil Dan Menengah (UMKM) di Ucok Kopi - Sondang Triana Hutapea; Dila Atmina Damanik; Muhammad Zul Apandi; Irwansyah Irwansyah; Elfina Okto Posmaida Damanik (CV. Ulil Albab Corp, 2024)
This study aims to determine the relationship between fixed costs and variable costs on sales at Ucok Kopi, Pematang Siantar. The type of research used in this study is quantitative descriptive research. The sample and population in this study are variable cost reports, fixed costs, and sales. Data processing in this study used SPSS 26 to determine the results of this study. It is known that, the data analysis technique performed is Multiple Linear Regression Analysis and Hypothesis Test (F Test). Where, it is known that Variable X is Variable Cost (X1) and Fixed Cost (X2) and Variable (Y) is Sales. The results of data analysis show that there is a positive relationship in each data analysis technique performed.